Intraspecific differentiation in seed flooding tolerance of Echinochloa crusgalli var. zelayensis population in shores of a giant reservoir along altitudinal gradients. (11th November 2020) - Liu, Songping; Lin, Feng; Su, Xiaolei; Ayi, Qiaoli; Niu, Hangang; Shi, Shaohua; Wan, Binna; Zeng, Bo; Zhang, Xiaoping
Abstract: Aims: In a large dam-regulated reservoir with regular hydrological pattern and strong flooding gradients across shore elevations, plants inhabiting in different shore elevations have to confront long-lasting flooding of differential intensities every year. Such persistent stress may lead to intraspecific differentiation of flooding tolerance in seeds. Echinochloa crusgalli var. zelayensis is a dominant annual plant in the shores of the Three Gorges Reservoir (TGR), which plays an important role in the shore vegetation. The objective of this study is to check whether intraspecific differentiation of seed flooding tolerance has occurred among E. crusgalli var. zelayensis populations in the TGR shores and whether such differentiation is associated with weak seed dispersal. Methods: We collected seeds of E. crusgalli var. zelayensis from different populations in the TGR shores, and then placed them at four elevations in the shores flooded by reservoir impoundment. Parameters reflecting seed flooding tolerance including post-flooding percentage of intact seeds, seed germinability and seedling emergence rate were investigated for the seeds from different populations and undergoing flooding of different intensities. Floating time of seeds and speed of water level rise during impoundment were examined, and used to quantify dispersal potential of seeds in the shores of the TGR when flooded. Important Findings: Both intact seed percentage and final seedling emergence rate after flooding significantly declined with increasing shore elevations where the seeds were collected, indicating that intraspecific differentiation in seed flooding tolerance has occurred among E. crusgalli var. zelayensis populations in the TGR shores after 7-year operation of the reservoir. The distance of seeds transported by rising water during reservoir impoundment was limited due to short-floating time of the seeds and relatively low speed of water level rise in the reservoir. This would be favourable to the development of intraspecific differentiation in seed flooding tolerance.